Correlation Analysis Between the Geriatric Nutritional Risk Index Hip Fracture in Male: Based on the National Health and Nutrition Examination Survey Database - Lan, Fangfang; Jiang, Kuihong (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
Hip fractures (HFs) are common in elderly patients and are associated with high mortality rates and functional impairment. Malnutrition has been shown to negatively impact postoperative survival rates in HF patients. However, the relationship between the Geriatric Nutrition Risk Index (GNRI) and the risk of HF remains unclear. This study aims to evaluate the association between GNRI and HF risk, with a particular focus on the elderly male population.We conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) for the periods 2007–2010, 2013–2014, and 2017–2018. Through multivariate regression analysis, we assessed the association between GNRI and HF and performed stratified and subgroup analyses to further explore this relationship. Additionally, we utilized restricted cubic splines (RCSs) to investigate the potential nonlinear relationship between GNRI and HF risk.The study found that gender significantly influenced the relationship between GNRI and HF (p for interaction = 0.002). In males, GNRI was significantly negatively associated with the risk of HF (OR < 1, p < 0.05). RCS analysis showed that the relationship between GNRI and HF risk in elderly males might be linearly negative. The critical threshold for GNRI was identified as 104.14, beyond which the risk of HF significantly decreased.This study demonstrates a linear negative correlation between GNRI and the risk of HF in elderly males, with a GNRI of 104.14 identified as the critical threshold for predicting the risk of hip fractures.
Keywords: Geriatric Nutritional Risk Index; cross-sectional study; gender; hip fracture; National Health and Nutrition Examination Survey; HF